Effect of trypanosomosis on the resumption of postpartum ovarian function and oestrus activity in Zebu cows - Tibbo, Markos; Mukasa-Mugerwa, E.; Abebe, G.; Mulatu, W. (Ethiopian Society of Animal Production, 2000)
The effect of trypanosomosis on the resumption of postpartum ovarian function and oestrus activity was studied in small East African zebu cows maintained under natural trypanosomosis challenge. This was done through the determination of milk progesterone levels using the enzyme linked immunosorbent assay (ELISA), packed cell volume (PCV), and darkground/phase contrast buffy coat examination to estimate the parasitic burden. The mean duration of postpartum anoestrus interval (PPAI) was longer (P<0.01) in infected than non infected cows (171.3 vs 96.1 days, respectively). This was consistent with the negative correlation (r = -0.2) between PPAI and mean PCV The correlation coefficients between infection and PCV was r = -0.5 indicating that the infection has a significant effect (P<0.01) on the PCV drop. On the other hand, a significant (P<0.05) variation between cycling non infected and acyclic ones, in that the non infected cows became pregnant early (within 41-98 days) whereas infected cows remained acyclic for a period of over four months (mean PCV was 25.3±0.5 vs 19. 6±1. 4 percent, respectively). Of the 17 postpartum cows studied, nine (53%) were acyclic for an average period of 151.2 days after calving (mean PCV 22.3±1.7%), three (18%) failed to conceive (mean PCV 23.6±1.8%), one (61) experienced prolonged luteal activity for over 70 days (mean PCV 22.1±1.7%) and three (18%) became pregnant (mean PCV 24.1±1.2%). Several of these reproductive disorders resulted from trypanosome infection.